Indberetning fra Landbrugskonsulent N. Otto Nielsen for Aaret 1915 til 31. Marts 1916. - Nielsen, N. Otto (Tidsskrift for Landøkonomi, 2018)
Indberetning fra Landbrugskonsulent N. Otto Nielsen for Aaret 1915 til 31. Marts 1916.